2008
DOI: 10.4103/0019-5154.43213
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial resistance to antibiotics in acne vulgaris: An in vitro study

Abstract: Background:Acne vulgaris is one of the most common skin disorders in youth especially during the puberty.Objective:This in vitro study was performed to determine the antibiotic resistance and sensitivity in acne vulgaris.Materials and Methods:Samples were collected from normal skin and nodulocystic and pustular skin lesions of one hundred youngsters (64 girls, 36 boys) among college students in the age range of 18-24 years old. The specimens were cultured individually on blood agar and Muller-Hinton media. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 14 publications
2
29
0
3
Order By: Relevance
“…Only 36.84% of the isolates were sensitive to tetracycline. Resistance to tetracycline in Staphylococcus aureus has been reported in the present study and in the study by Hassanzadeh et al [3] It may be due to extensive tetracycline usage in the past. It has been suggested that tetracycline, which becomes concentrated in inflamed lesions and has been the mainstay of acne treatment for two decades, could act by inhibiting neutrophil chemotaxis rather than its antibacterial actions.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Only 36.84% of the isolates were sensitive to tetracycline. Resistance to tetracycline in Staphylococcus aureus has been reported in the present study and in the study by Hassanzadeh et al [3] It may be due to extensive tetracycline usage in the past. It has been suggested that tetracycline, which becomes concentrated in inflamed lesions and has been the mainstay of acne treatment for two decades, could act by inhibiting neutrophil chemotaxis rather than its antibacterial actions.…”
Section: Discussionsupporting
confidence: 53%
“…This is in contrast to reports which implicated both Staphylococcus epidermidis and Propionibacterium acnes as bacteria causing acne vulgaris. [3] By using a genetically based strategy (Analysis of 16S rRNA genes) with sensitivity and discriminatory power surpassing those of culture-based methods, Bek-Thomsen et al demonstrated that the bacterial microbiota of follicles from acne-affected subjects showed more, although still very limited, diversity. The microbiota was dominated by Propionibacterium acnes and Staphylococcus epidermidis, which were the only species consistently found.…”
Section: Discussionmentioning
confidence: 99%
“…TCS is used as an antibacterial agent in dermal products against acne vulgaris, which is thought to be caused primarily by S. aureus (10,32). Mean zone of inhibition (mm±SD) could be listed in order as: The microbiological studies revealed that the formulations were effective, and this antimicrobial effect was significantly greater than TCS suspension in water and commercial product but the same for both organogels (Fig.…”
Section: Triclosan In Mw Gelmentioning
confidence: 99%
“…Ayrıca stafilokokların da akne vulgariste olası patogenetik rolü olduğuna dair önemli in vitro bulgular vardır. Yapılan bir çalışmada akne açısından değerlendirilen katılımcıların %53'ünün Staphylococcus epidermidis ile kolonize olduğu gösterilmiştir 2 . Kırk yılı aşkın süredir akne tedavisinde kullanılan antibiyotikler, hala sıklıkla bu amaçla reçete edilmektedir.…”
Section: Introductionunclassified